Britain and the American South : from colonialism to rock and roll - Lambert, Franklin T.; Ward, Joseph P., 1965- (Chancellor Porter L. Fortune Symposium in Southern History series., 2003)
In this text, historians analyse central aspects of the cultural exchanges between Britain and the American South. They consider the British influence upon Southern institutions and cultural formations such as religion, gentility, slavery and music.